Estimation of Glycemic Index of Liver Nutritional Supplement and its Importance in Liver Nutrition - Rachana Bhoite; Shobana Shanmugam; Varalakshmi Lalithya Pratti; Vinita Satyavrat; Gayathri Rajagopal; Ranjit Mohan Anjana; Viswanathan Mohan (Journal of Human Health Research, 2023)
A global increase in incidence of chronic liver disease (CLD) indicated the necessity of dietary and lifestyle modification. Low glycemic index (GI) diet was reported to have a significant role in controlling diabetes caused by liver dysfunction. The International Standards Organisation (ISO) has standardized the determination of GI of a food in healthy individuals. This study aimed to estimate GI value of a high protein, energy dense liver nutritional supplement. This cross-over randomized controlled study randomly allotted 15 participants to consume either reference food 27.5 gm glucose (glucose monohydrate) or 77 gm nutritional supplement (equivalent to 25 gm of available carbohydrates); switching to another arm was done after 3 days wash-out period. After overnight fast, blood samples were collected at 15, 30, 45 and 60 minutes post-consumption of s upplement or reference food. The GI was calculated from the incremental area under the blood glucose response elicited by the nutritional supplement as a percentage of the response after consumption of 27.5 gm of glucose (glucose monohydrate) by the same participant using a standard formula. Mean GI of the nutritional supplementwas estimated as 11.4 ± 2.4.With the consumption of this nutritional supplement, the blood glucose levels were reduced at all postprandial time points, compared to the reference food. The liver nutritional supplement tested has a low GI, and comparatively slower and more sustained blood glucose response. Therefore, it can be used in patients with CLD to prevent CLD-associated metabolic complications and improve health outcomes and quality of life.
Keywords: Blood glucose